Transfer factor : basic properties and clinical applications - Gottlieb, A. Arthur (Abraham Arthur), 1937-1998; Kirkpatrick, Charles H., 1931-; Ascher, Michael S. (Academic Press, 1976)
Transfer Factor: Basic Properties and Clinical Applications covers papers about transfer factor.